An "ex situ" microbial process for the removal of heavy metals from polluted soil: A case study of Ada rice field, Adani, Enugu State, Nigeria. Issue 3 (2nd October 2017) - Nwuche, Charles O.; Ujam, Oguejiofo T.; Ihedioha, Janefrances N.; Chime, Charles C.
ABSTRACT: An "ex situ" microbial method for the removal of heavy metals from soil is described. Elemental sulfur was added to generate the lixiviant in shaker flask experiments in which soil sampled from a polluted agricultural field was treated. The biotic oxidation of sulfur to sulfuric acid resulted in significant drop in pH of the bioleaching liquor from 6.94 to 1.8 after 50 days. In batches operated at very low (10 g/kg) sulfur concentrations, pH changed from 6.94 to 5.45. The 50 g/kg soil sulfur concentration was found to be most beneficial to the solubilization process because more than 95% of metals such as zinc (Zn), cadmium (Cd), and nickel (Ni) were recovered while approximately 67% of manganese (Mn) got solubilized. The least concentration of dissolved metals was lead (Pb) – (25%) and chromium (Cr) – (10%). Sulfate accumulation rose to 47% in samples spiked with 50 g/kg soil of sulfur. At lower sulfur concentrations, the sulfates generated were higher than the amount of sulfur added. The microbial process compared well to the abiotic process involving extraneous addition of sulfuric acid except that very high concentrations of acid had to be used. The treatment of the bioleaching wastewater promoted precipitation of the dissolved metals into insoluble hydroxides making discharge of the effluent into the environment safe. The leached soil recovered sufficiently for agricultural use after quick lime and animal manure was used to improve, stabilize, and restore its physical, chemical, and biological conditions.